Manipulador robótico para poda automática (Projecto ROMOVI) - José Nuno Gomes de Brito (2018)
One of the biggest challenges of the agricultural robotics is the development of robots that are able to execute automatic pruning in a efficient way. This master thesis aims to study specific manipulator and its pruning tool that will be installed in AGROB V16 robot for application in the context of automatic pruning tasks for vineyard context. It will be necessary to implement a simulated environment, that has AGROB V16 robot and vineyard, in order to study the different approaches for trajectory planning. The tests of the different state of art planners (open source) will be done in the ROS platform and it is divided in two main components: simulation and laboratory environment. The visual perception component of the vine won't be taken in account in the context of this work proposal.